2018
DOI: 10.1158/0008-5472.can-17-1138
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Single-Cell Genomics in Diagnostic Evaluation of Prostate Cancer

Abstract: A distinction between indolent and aggressive disease is a major challenge in diagnostics of prostate cancer. As genetic heterogeneity and complexity may influence clinical outcome, we have initiated studies on single tumor cell genomics. In this study, we demonstrate that sparse DNA sequencing of single-cell nuclei from prostate core biopsies is a rich source of quantitative parameters for evaluating neoplastic growth and aggressiveness. These include the presence of clonal populations, the phylogenetic struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…For this reason, single-cell analysis has proved to be very useful for the study of cellular subpopulation in many solid human tumors, such as breast [ 1 ], kidney [ 2 ], colon [ 3 ] and prostate [ 4 ] cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, single-cell analysis has proved to be very useful for the study of cellular subpopulation in many solid human tumors, such as breast [ 1 ], kidney [ 2 ], colon [ 3 ] and prostate [ 4 ] cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the temporal order in which mutations accumulate in hematological neoplasms and in many solid human tumors, such as breast [ 1 ], kidney [ 2 ], colon [ 3 ] and prostate [ 4 ] cancers, is fundamental to understand the clonal landscape underlying disease evolution. In recent years, single-cell genomics has been developed as a powerful method for reconstructing the complex cancer pathogenesis [ 5 ] and its heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…We used single-nuclei DNA data previously generated from a previous WGA method (Alexander et al 2018). Briefly, single nuclei were deposited into individual wells in a 96-well plate and amplified using GenomePlex WGA4 kit (Sigma-Aldrich WGA4-50RXN) according to the manufacturer's instructions.…”
Section: Single-nuclei Wga Methodsmentioning
confidence: 99%
“…The method works on nuclei isolated from frozen tumor biopsies, and we illustrate this using previously published clinical material (Alexander et al 2018). Figure 2C shows the pathology image of a region from a prostate with a Gleason 9 lesion, assessed by pathologists as 60% cancer.…”
Section: Copy Number Profiles From Mixed Populationsmentioning
confidence: 99%
See 1 more Smart Citation